Effect of Tonsillectomy on Recurrence of Psoriasis - M Musharaf Baig (Journal of Rawalpindi Medical College, 2013)
Background :To assess the effectiveness of tonsillectomy in the management of guttate psoriasis. Methods: In this descriptive study, fifty patients with psoriasis, along with chronic tonsillitis were included. All subjects who showed the signs of any systemic disease were excluded from study. Patients underwent tonsillectomy and then the effects of tonsillectomy on skin patches were observed in all the patients. Results: The patient’s age ranged between 13-27 years. Majority (60%) were males. Forty four percent showed complete cure after tonsillectomy while 12% showed partial cure. Conclusion: Tonsillectomy does have a beneficial effect on course of psoriasis.